Tinjauan Yuridis Peran Notaris dalam Penyelesaian Sengketa Waris di Indonesia - Salma Salsabila; Ika Kartika Sari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Various jurisdictions including Indonesia, inheritance disputes often involve complex interactions between cultural, religious, and legal systems. The role of the notary as a facilitator of disputes outside the court by prioritizing legal principles and the notary code of ethics. Succession disputes have triggered conflicts among heirs that have been prolonged through court proceedings. Notaries act as facilitators utilizing legal expertise to explain the rights and responsibilities of all parties involved, by encouraging the creation of a transparent communication and mediation atmosphere. The method used is an empirical method with a qualitative approach method. This research aims to examine how notaries play a role in facilitating dispute resolution, and convey the obstacles faced by notaries. This research emphasizes the role of notaries in ensuring that inheritance disputes are resolved peacefully and fairly. However, there are obstacles in ensuring fairness and preventing overlap in regulations. Strengthening understanding of the code of ethics and understanding of the rules is needed to support the performance of notaries in these situations.